2020
DOI: 10.1177/2050640620937913
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of lactulose plus paraffin vs polyethylene glycol in functional constipation: a randomised clinical study

Abstract: Background Few head-to-head comparisons of the different classes of laxatives have been conducted. Objective The objective of this work is to compare the efficacy of lactulose plus paraffin vs polyethylene glycol in the treatment of functional constipation (non-inferiority study). Methods This randomised, parallel-group, multicentre phase 4 study recruited patients with functional constipation diagnosed according to Rome III criteria. Patients received lactulose plus paraffin or polyethylene glycol for 28 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…showed that lactulose 3350 could relieve chronic constipation in adults and had no side effects in patients [31] . Lee et al also showed that administration of lactulose 3350 in constipation treatment was able to relieve constipation in adults [32] .…”
Section: Discussionmentioning
confidence: 99%
“…showed that lactulose 3350 could relieve chronic constipation in adults and had no side effects in patients [31] . Lee et al also showed that administration of lactulose 3350 in constipation treatment was able to relieve constipation in adults [32] .…”
Section: Discussionmentioning
confidence: 99%
“…At least one adverse event occurred in 11.2% of patients in the lactulose plus paraffin group and in 14.2% of patients in the PEG group, most of which were of mild or moderate severity and unrelated to study drugs. This study, for the first time, established the non-inferiority of lactulose (in combination with paraffin) compared to PEG in the alleviation of symptoms of functional constipation in adults [37].…”
Section: Mechanism Of Actionmentioning
confidence: 92%
“…More recently, a multicenter RCT investigating escalating doses of lactulose in 250 patients with chronic constipation receiving 13, 26, or 39 g/day of crystal lactulose, respectively, for two weeks found that the 26 and 39 g doses induced significantly and dose-dependently greater increases in spontaneous bowel movements after 1 (primary endpoint) and 2 weeks, respectively, compared to placebo. With these doses, also significant improvements in stool consistency and • Increased frequency of defecation and number of bowel movements (9,10,(20)(21)(22)(23)(27)(28)(29)(30)(31)(32)(33)(34)36,37) • Relieved postpartum constipation (24)(25)(26) • Prebiotic properties (9,(44)(45)(46)(47)(48)(49) Tolerance and safety…”
Section: Benefits Of Lactulose For Patients With Constipationmentioning
confidence: 99%